Ricardo Palma, José Dávila Condemarín and the Quixote - Holguín Callo, Oswaldo (2020)
In 1905, inspired by the fourth centenary of the publication of the first part of the Cervantes’ famous novel, Palma wrote «Sobre el Quijote en América», a reminiscent and bibliographical article in which he pointsout that it is not a tradition. In the above-mentioned article, he discovers the origin of the «very curious story» narrated in 1877 by José Dávila Condemarín, a respected civil servant, about the arrival of the first Quixote in Lima. As a colophon, Palma’s cervantofilia is discussed.